Growth Yield and Nutrient Requirement of Adlay (Coix lacryma-jobi L.) Applied with Different Levels of Nitrogen in Bukidnon Philippines - MiÃ±oza, Michelle Mae Recla; Planas, Juvelyn Yacunas; Labajo, John Rey Natinga (Plantropica: Journal of Agricultural Science, 2023)
The study was conducted at Agricultural Experiment Center, Central Mindanao University, Musuan, Maramag, Bukidnon from August 2018 to January 2019 with the following objectives: (1) evaluate the effects of different rates of N on the soil chemical properties at harvest; (2) evaluate the effects of different rates of N on the growth of adlay; and (3) determine the cost and return analysis of adlay applied with different rates of Nitrogen. The field experiment was laid out in Randomized Completely Block Design (RCBD) with six treatments, replicated thrice with 18 experimental units. The fertilizer rate used for the experimental site was 50 kg of P2O5 ha-1 and 20 kg of K2O ha-1. Different Nitrogen rates were used (0, 30, 60, 80, 100, 120 kg ha-1). Based on the results, soil properties, including pH and extractable P at harvest, were noted to be not significantly affected by the application of different treatments; however, organic matter and exchangeable K were significantly affected by the treatments. Treatment 4, with 80 kg N ha-1,has the highest grain yield and return on investment, hence the most economical treatment.